Effect of a feed additive based on a mix of condense and hydrolysable tannins (ByPro®) on lactating dairy cows milk production performance - Alejandro R. Castillo; Martin Pol; Mónica Gaggiotti; Julio A. Di Rienzo; Damiano Cavallini (Tropical Animal Health and Production, 2025)
The objective of this research was to evaluate the effect of a commercial mix of condensed and hydrolysable tannins feed additive to lactating dairy cows. Two high-scale dairy farm units, similar management and diets were used. All lactating cows in one unit were fed with the mix of tannins (ByPro ® 0.3%DMI), the other unit was the Control. Cows were categorized per DIM, 0 to 30, 31 to 120, 121 to 365, and more. Milk yield and composition was evaluated in all the lactating cows in each dairy unit at time 0, (initial), and after 4 weeks of supplementation (final). A linear model was adjusted for each variable. Estimated DMI and diets were similar in both dairy units, averaging 25.5 kg DMI/cow, as well as feed ingredients, dietary nutrient contents, and milk yield (34 kg milk/cow per day). Milk yield, from 0 to 365 DIM was increased ( P < 0.01) on supplemented cows (+ 2.3 ± 0.33 L milk/cow.d), with no effect on milk fat and protein contents. High data variability was observed on cows with 0–30 DIM, milk fat and protein content were reduced by ByPro without effect on milk yield. Positive responses of ByPro ® on milk, milk fat and protein contents from 31 to 120 and 121–365 DIM were observed, + 3.6 and + 3.2 kg milk/cow.d; +0.27% fat and + 0.21% protein; and + 0.17% fat, + 0.11% protein; respectively. The mix of tannins increased milk lactation performance on cows with more than 30 DIM.